The Influence of Motivation and Working Discipline on Employee Performance - Deni Budiana; Ayu Siti Syamsiah; Ani Yunaningsih (Almana: Jurnal Manajemen dan Bisnis, 2023)
Motivation is a person's encouragement to take action to achieve his goals. Discipline is a person's behavior to obey the rules based on awareness and willingness to accept sanctions when violating the rules. Performance is the work achieved by an employee based on the actions and responsibilities of each employee at a certain time. This study aims to determine the influence of motivation and work discipline on employee performance in the marketing division of PT. Len Industri (Persero) Bandung. The type of research used is a quantitative approach method using primary and secondary data sources. The total population in this study was 120 employees in the marketing division of PT. Len Industri (Persero) Bandung, with a sample of 93 employees. Data analysis used path analysis and hypothesis testing using the test and F-test which were processed using SPSS Version 22 program. Based on the results of the study, it can be concluded that partially both motivation and work discipline variables have a positive and significant effect on employee performance. Meanwhile, simultaneously motivation and work discipline have a positive and significant effect on employee performance.